2009
DOI: 10.1167/9.11.17
|View full text |Cite
|
Sign up to set email alerts
|

Orientation-tuned suppression in binocular rivalry reveals general and specific components of rivalry suppression

Abstract: During binocular rivalry (BR), conflicting monocular images are alternately suppressed from awareness. During suppression of an image, contrast sensitivity for probes is reduced by approximately 0.3-0.5 log units relative to when the image is in perceptual dominance. Previous studies on rivalry suppression have led to controversies concerning the nature and extent of suppression during BR. We tested for feature-specific suppression using orthogonal rivaling gratings and measuring contrast sensitivity to small … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
40
0

Year Published

2010
2010
2014
2014

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 44 publications
(44 citation statements)
references
References 53 publications
4
40
0
Order By: Relevance
“…These latter studies argue that the magnitude of suppression during rivalry depends on the similarity in feature content between the competing images. For example, sensitivity to oriented probes presented in a suppressed image depends on the orientation difference between the probe and the suppressed image (Stuit et al, 2009). A similar dependency was shown for spatial frequency content.…”
Section: Introductionmentioning
confidence: 54%
See 1 more Smart Citation
“…These latter studies argue that the magnitude of suppression during rivalry depends on the similarity in feature content between the competing images. For example, sensitivity to oriented probes presented in a suppressed image depends on the orientation difference between the probe and the suppressed image (Stuit et al, 2009). A similar dependency was shown for spatial frequency content.…”
Section: Introductionmentioning
confidence: 54%
“…Traditionally, this suppression of an image during binocular rivalry is considered to be non-selective: All inputs from the suppressed eye (i.e., the eye to which the suppressed image was presented) are thought to be uniformly affected (e.g., Blake, 1989;Blake & Fox, 1974;Blake & Logothetis, 2002;Blake, Westendorf, & Overton, 1980;Fox & Check, 1966, 1968Freeman, Nguyen, & Alais, 2005;Nguyen, Freeman, & Wenderoth, 2001;Wales & Fox, 1970). However, evidence that challenges this view is accumulating (Alais & Parker, 2006;O'Shea & Crassini, 1981;Paffen, Alais, & Verstraten, 2005;Stuit, Cass, Paffen, & Alais, 2009;Vergeer & van Lier, 2010). These latter studies argue that the magnitude of suppression during rivalry depends on the similarity in feature content between the competing images.…”
Section: Introductionmentioning
confidence: 99%
“…Although motion streaks are not usually perceived, they do activate orientation-tuned neurons to induce tilt illusions and aftereffects (Apthorp and Alais, 2009; Apthorp et al, 2010). In a binocular rivalry study, it was shown that “streaks” from fast moving dot patterns produce orientation-tuned rivalry suppression (Apthorp et al, 2009; Stuit et al, 2009), even though no orientation is present in the static stimulus. In some cases, then, apparent examples of motion rivalry may indeed be cases of spatially-triggered rivalry.…”
Section: Discussionmentioning
confidence: 99%
“…This view of suppression dovetails with other findings suggesting that interocular suppression works by reducing effective stimulus contrast or contrast gain of stimulus-evoked responses within early stages of visual processing (Watanabe et al, 2004; Tsuchiya et al, 2006; Yuval-Greenberg and Heeger, 2013). However, this is only half of the story, for there is also evidence for an additional selective component to interocular suppression (Stuit et al, 2009). In the following paragraphs, we review evidence for selectivity obtained using the CFS technique to induce interocular suppression.…”
Section: Introductionmentioning
confidence: 99%
“…Considered together, the processing of a stimulus under CFS will be adversely impacted in general (non-selective suppression) but to an extent that depends on the similarity between that stimulus and the stimulus doing the suppression [feature-selective suppression, similar to that described by Stuit et al (2009), for conventional binocular rivalry]. This is important for at least two reasons.…”
Section: Introductionmentioning
confidence: 99%